2004
DOI: 10.5172/conu.17.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Nurse-academics’ scholarly productivity: Perceived frames and facilitators

Abstract: The reward system within Universities remains focused on research, with a benchmark of scholarly productivity, especially in relation to promotion. Despite their relative newness to the tertiary system, nurse academics are judged by the same standards as other disciplines. This study sought to examine factors that constrained and/or facilitated scholarly productivity. The study used a questionnaire survey technique to establish current productivity levels, and frame and facilitating factor theory and analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 8 publications
4
32
0
Order By: Relevance
“…Byrne and Keefe (2002), in their published work review, noted that mentoring of faculty is an important resource for conducting research. However, Roberts and Turnbull (2004) reported that junior nursing faculty do not have sufficient mentorship from senior faculty because they do not understand how to effectively provide research mentorship. Other academic-centered issues affecting research productivity also have been reported; having a research assistant has a positive influence on research productivity, while duties outside of research have a negative impact.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Byrne and Keefe (2002), in their published work review, noted that mentoring of faculty is an important resource for conducting research. However, Roberts and Turnbull (2004) reported that junior nursing faculty do not have sufficient mentorship from senior faculty because they do not understand how to effectively provide research mentorship. Other academic-centered issues affecting research productivity also have been reported; having a research assistant has a positive influence on research productivity, while duties outside of research have a negative impact.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of mentoring and career planning difficulty are reminiscent of previous research results. Roberts (1997) and Jacelon, Zucker, Staccarini and Henneman, 2003 reported that mentorships facilitate publication. Byrne and Keefe (2002), in their published work review, noted that mentoring of faculty is an important resource for conducting research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations